2020
DOI: 10.1080/19371918.2020.1806984
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Covid-19 Pandemic on Syrian Refugees in Turkey: The Case of Kilis

Abstract: The objective of this study; is to find out the sensitivity, the concern that are created by the Covid-19 pandemic on the Syrian refugees, who live in Kilis province of Turkey and have different life standards and status and to find out their possibilities and attitudes of prevention from and combating the pandemic. The data of the study were collected between 12-16 April 2020 by applying a questionnaire on 414 refugees. According to the study results, it has been discovered that the refugees have concerns abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 3 publications
1
14
0
3
Order By: Relevance
“…Asylum seekers and undocumented migrants avoided seeking health care during the pandemic due to lack of trust in the system and fear of jail and deportation [ 7 , 24 , 33 ], which made it difficult to determine the exact burden of the COVID-19 pandemic case numbers, admissions, and deaths. However, multiple studies that examined differential disease consequences reported a disproportionately higher proportion of COVID-19 cases among asylum seekers and undocumented migrants compared to the general population [ 30 , 32 , 35 , 36 , 41 , 48 ]. For instance, the positivity rate at a community testing centre in the U.S. was 10 times higher among undocumented migrants than among non-Hispanic whites (91.6% vs. 81.7%, p < 0.001) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Asylum seekers and undocumented migrants avoided seeking health care during the pandemic due to lack of trust in the system and fear of jail and deportation [ 7 , 24 , 33 ], which made it difficult to determine the exact burden of the COVID-19 pandemic case numbers, admissions, and deaths. However, multiple studies that examined differential disease consequences reported a disproportionately higher proportion of COVID-19 cases among asylum seekers and undocumented migrants compared to the general population [ 30 , 32 , 35 , 36 , 41 , 48 ]. For instance, the positivity rate at a community testing centre in the U.S. was 10 times higher among undocumented migrants than among non-Hispanic whites (91.6% vs. 81.7%, p < 0.001) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…After discounting duplicate articles, 28 publications were considered relevant and thus included in the review. As shown in Table 2, these publications present a varied geographic emphasis, ranging from the Syrian refugee response in Turkey 12 to the challenges faced by refugees from Bhutan and Burma in the US. 13 The single most widely represented regional focus, with a total of 11 publications, is on high-income countries with a particular emphasis on Europe, the US and Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2020) indicated that community-based professional social work must be expanded and multisectoral collaboration should be promoted between governmental bodies and NGOs in response to the needs of a migrant household in developing countries. According to Budak and Bostan (2020), refugees were generally sensitive to COVID-19 and able to follow the rules, but some were not aware of the seriousness of the pandemic because they did not have enough information. The NGOs did play a vital role by offering psychosocial support services to refugees; however, practical challenges included the following: being unprepared for tele-social work, a decrease in financial resources, and increasing barriers to resources (Nisanci et al, 2020).…”
Section: Resultsmentioning
confidence: 99%